1979
DOI: 10.1080/00039896.1979.10667450
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Aberrations Induced by Occupational Exposure to Mercury

Abstract: The incidence of chromosome aberrations was studied by peripheral blood incubation (52 hr, the last 4 hr in the presence of Colcemid) using a modification of the Evans' technique in twenty-two men exposed to either vapors of metallic mercury (Group I) or organic mercury (Group II). Mercury concentrations of the work areas frequently exceeded the Maximum Allowable Concentrations in the past. During the year proceding the investigation, mercury values ranged between 0.15 and 0.44 mg/m3. None of the investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Since after inhalation of elemental mercury vapour in the blood elemental mercury is oxidised to mercuric mercury (ATSDR, 1999) the following section summarises genotoxicity in human lymphocytes after exposure towards elemental mercury. In human lymphocytes genetic damage (in terms of chromosome aberrations) has been observed after occupational exposure to elemental and organic mercury (Verschaeve et al, 1976;Popescu et al, 1979;Cebulska-Wasilewska et al, 2005); sister chromatid exchanges (Popescu et al, 1979;Cebulska-Wasilewska et al, 2005) and DNA damage as measured by the alkaline version of the Comet assay (Cebulska-Wasilewska et al, 2005) were not statistically significantly increased in these studies. Repair efficiencies in lymphocytes of 25 workers exposed to elemental mercury vapour were reduced compared with 50 individuals nonoccupationally exposed, as measured by the X-rays challenge assay (Cebulska-Wasilewska et al, 2005).…”
Section: Genotoxicitymentioning
confidence: 81%
“…Since after inhalation of elemental mercury vapour in the blood elemental mercury is oxidised to mercuric mercury (ATSDR, 1999) the following section summarises genotoxicity in human lymphocytes after exposure towards elemental mercury. In human lymphocytes genetic damage (in terms of chromosome aberrations) has been observed after occupational exposure to elemental and organic mercury (Verschaeve et al, 1976;Popescu et al, 1979;Cebulska-Wasilewska et al, 2005); sister chromatid exchanges (Popescu et al, 1979;Cebulska-Wasilewska et al, 2005) and DNA damage as measured by the alkaline version of the Comet assay (Cebulska-Wasilewska et al, 2005) were not statistically significantly increased in these studies. Repair efficiencies in lymphocytes of 25 workers exposed to elemental mercury vapour were reduced compared with 50 individuals nonoccupationally exposed, as measured by the X-rays challenge assay (Cebulska-Wasilewska et al, 2005).…”
Section: Genotoxicitymentioning
confidence: 81%
“…Versc haeve et al (6) observe d an increased prevalence of chromosome aberrat ions in 28 subjects exposed to various mercury compounds, but the resu lts were not confirmed in a later study (7) . Popescu et al (8) found an increa se in chromosome aberrations, but no increase in chromatid-type aberration s in four subjects with repeatedly high urinary mercury concentrations reaching 890 ug . I-I (4450 nmol .…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, micronucleus assay indicated an accumulation of cytogenetic damage in lymphocytes after exposure to mercury vapor (4) or mercury fulminate (5). Previous studies on humans during ongoing exposure to inorganic mercury compounds showed conflicting results when other cytogenetic methods were used (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The ability of inorganic mercury to induce gene mutations seems, however, to be low (3,4). Cytogenetic in vivo studies have, in most cases, shown no effects on human chromosomes (6)(7)(8)(9). Only few studies of cancer in animals after exposure to mercury have been reported, and none used the inhalation of mercury vapor as the method of exposure (10,11).…”
mentioning
confidence: 99%